2013
DOI: 10.5402/2013/280395
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E Is a Nephroprotectant Agent in Male but Not in Female in a Model of Cisplatin-Induced Nephrotoxicity

Abstract: Background. The role of gender for nephroprotectant agent such as vitamin E in cisplatin- (CP-) induced nephrotoxicity has not been documented yet. Methods. One group from each gender of Wistar rats received a single dose of CP (7 mg/kg; i.p) and was treated with vitamin E (1 g/kg/day) for 7 days, and they were compared with similar gender in the control group. Results. The serum levels of blood urea nitrogen (BUN) and creatinine (Cr) in male animals treated with CP was not different from the control group, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…Additionally, another similar study, researcher confirmed that administration of vitamin E (1 g/kg/d) for 7 days prevented cisplatin‐induced nephrotoxicity just in male rats. After vitamin E administration to each gender of Wistar rats received a single dose of cisplatin (7 mg/kg; IP), it was found that although the serum levels of blood urea and creatinine in male cisplatin‐treated animals was not different from the control group, it was significantly different in the female rats ( P < 0.05) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, another similar study, researcher confirmed that administration of vitamin E (1 g/kg/d) for 7 days prevented cisplatin‐induced nephrotoxicity just in male rats. After vitamin E administration to each gender of Wistar rats received a single dose of cisplatin (7 mg/kg; IP), it was found that although the serum levels of blood urea and creatinine in male cisplatin‐treated animals was not different from the control group, it was significantly different in the female rats ( P < 0.05) …”
Section: Resultsmentioning
confidence: 99%
“…The potential protective effects of vitamin E administration, alone or in combination with other agents have been assessed in several clinical or preclinical studies . For example, Varzi et al demonstrated that vitamin E in combination with silymarin could ameliorate the nephrotoxicity induced by gentamicin at a dosage of 20 mg/kg, once daily for 9 days, in dogs.…”
Section: Introductionmentioning
confidence: 99%
“…They have also reported that the vasodilator effect of NO improves the blood flow which can, in its own turn, decrease tissue damage (24). In another study, Jilanchi et al have shown that, in cisplatin nephrotoxicity, vitamin E modified BUN and Cr level in male rates; while this effect was not observed in female rats (22). Actually, antioxidant vitamins act as free radical scavengers, therefore, the decrease of kidney damage can improve BUN and Cr level.…”
Section: Discussionmentioning
confidence: 98%
“…The first and second groups, each including nine rats, received gentamicin (80 mg/kg/d) for 9 days (21). Similarly, the third and fourth groups, each including nine rats, received a regular dose of gentamicin (80 mg/kg/d) + vitamin E (1 g/kg/d) for 9 days (22). The fifth and sixth groups, each consisting of eight animals, obtained a continuous dose of gentamicin (80 mg/kg/d) + vitamin C (250 mg/kg/d) for 9 days (23).…”
Section: Experimental Protocolmentioning
confidence: 99%
“…However, detrimental changes in NRCM secondary to higher levels of ROS cannot be prevented, as reflected by the findings in the post-treatment group (Jilanchi et al, 2013). As with this study, the oxidative damage occurring after H 2 O 2 induction most probably could not be repaired by TRF, hence giving rise to progressive cell death (Han et al, 2004).…”
Section: Discussionmentioning
confidence: 47%